2020
DOI: 10.3390/ma13133014
|View full text |Cite
|
Sign up to set email alerts
|

The Luminescence of 1,8-Diazafluoren-9-One/Titanium Dioxide Composite Thin Films for Optical Application

Abstract: The investigation of innovative label-free α-amino acids detection methods represents a crucial step for the early diagnosis of several diseases. While 1,8-diazafluoren-9-one (DFO) is known in forensic application because of the fluorescent products by reacting with the amino acids present in the papillary exudate, its application for diagnostic purposes has not been fully investigated. The stabilization of DFO over a transparent substrate allows its complexation with biomolecules for the detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…In addition, using the quantum chemical calculations, we confirmed the energetic tendency of the DFO molecule to aggregate with a preference for the dimer structure formation. This result is strongly compatible with our recent publication results [ 21 , 22 , 23 ], where we confirmed the aggregation ability of DFO in ethanol and the emission of DFO aggregates in ethanol with an emission maximum at a similar wavelength as the DFO complex with glycine (an alpha-amino acid). These results significantly affect the application of DFO in Friction Ridge Analysis and are predictive of the application of DFO on different types of substrates with different surface energy characteristics.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, using the quantum chemical calculations, we confirmed the energetic tendency of the DFO molecule to aggregate with a preference for the dimer structure formation. This result is strongly compatible with our recent publication results [ 21 , 22 , 23 ], where we confirmed the aggregation ability of DFO in ethanol and the emission of DFO aggregates in ethanol with an emission maximum at a similar wavelength as the DFO complex with glycine (an alpha-amino acid). These results significantly affect the application of DFO in Friction Ridge Analysis and are predictive of the application of DFO on different types of substrates with different surface energy characteristics.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, it is worth noting that aggregation processes are often overlooked in the interpretation of spectroscopic properties, as evidenced by current procedures for the visualization of dactyloscopic traces with DFO. DFO working solutions contain high concentrations of DFO, and in the process of visualization of dactyloscopic traces, not only DFO complexes with amino acids but also DFO aggregates are involved, as indicated by our previous work [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…In the previous work, the difference of dipole moments in the ground and excited states was calculated for the free DFO molecule and the hydrogen‐bonded complex (DFO + polar protic solvent). It has been confirmed that also specific solvent effects occur resulting from the interaction of the fluorophore with protic solvents (DFO dissolved in protic solvents, both nonspecific and specific [hydrogen bonding] interactions) [5,15].…”
Section: Resultsmentioning
confidence: 99%